Performance of biogas and its benefits economic partner in the sustainable rural development of the communities altoandinas.Ancash - Peru - Taramona Ruiz, Luis Alberto (2017)
In the present investigation it will benefit the rural population of the High Andean communities, that adopt biogas and biofertilizer as alternative energy and organic fertilizer, respectively; As they will have at their disposal an ecological fuel and organic fertilizer throughout the year, improving their quality of life.For this purpose, tubular biodigesters of PVC geomembrane of 8 and 12 m3 of total volume (1.27 m in diameter and 6.7 to 10 m in length) were used, with 6 and 9 m3 of working volume, respectively, occupied By the manure mixture of cattle: water in the proportion 1: 5. Biodigesters were installed in the Andean communities.Ancash. Peru. Based on the results obtained, at 38 days of loading the biodigester, the biogas produced reached a pressure of 10 cm of water throughout the system. For all this activity, it was required an operating time of the kitchen to biogas of two burners of 5 hours on average. Similar results were obtained in the evaluation of the biogas yield as fuel of a lamp adapted to operate to biogas.